To Study The Correlation of Body Mass Index With Serum Cholesterol Level In Youth: To Study The Correlation of Body Mass Index With Serum Cholesterol Level In - Patel, Kruti; Bachlaus, Neeta; Chaudhari, Hemangini; Parmar, Dharitri (National Journal of Integrated Research in Medicine, 2018)
Body mass index has been associated with changes in serum cholesterol levels. Aim of our study was to determine the serum cholesterol in the youth of Surat city and to associate it with the body mass index (BMI). Method: This cross-sectional study was done among 100 healthy subjects aged 15-24 years. By using enzymatic method TC was estimated and TC â‰¥ 200 mg/dl was defined as hypercholesterolemia as per WHO/IASO/IOTF (2000). All cases are classified into BMI categories. The range of TC found in the study groups was 124-220 mg/dl. Result: The results indicate that mean cholesterol level in males and females were 140-200 mg/dl and 139-192 mg/dl respectively. Prevalence of hypercholesterolemia was 16% in the study group. We found positive correlation of TC and BMI in males (r = 0.63, p<0.05) and in females (r = 0.66, p< 0.66). Conclusion: So, we conclude that the youths who are overweight should advise routine cholesterol checkup. So preventive measures can be adopted to avoid itâ€™s complications in future.[Kruti P NJIRM 2017; 8(4):85-90]